The root of all evil : an exposition of prejudice, fundamentalism, and gender imbalance - Mijares, Sharon G. (Sharon Grace), 1942- (Imprint Academic, 2007)
Demonstrates that the essence of love and tolerance at the core of all religions, of all great traditions, is universal. This title explores the roots of the world's evils in fundamentalism and patriarchy.